ACHIEVEMENT OF MINIMUM SERVICE STANDARDS (SPM) PRODUCTIVE AGE IN BOGOR CITY - Apriyanthi, Ria; Fauziah, Munaya; Ernyasih, Ernyasih (AN-NUR: Jurnal Kajian dan Pengembangan Kesehatan Masyarakat, 2024)
Minimum Service Standards (SPM) in the health sector is a health service quality policy that every citizen has the right to obtain. The SPM in the health sector consists of 12 basic services, one of which is the Productive Age Service with a target of 100% of the productive age being carried out for Early Detection of Non-Communicable Diseases which has not yet reached the target. The aim of this research is to determine the challenges and problems related to regional policy, human resources, the environment, funding infrastructure and facilities faced by SPM in the health sector and to prepare draft policy recommendations to achieve Minimum Service Standards for the productive age in Bogor City in 2024. This research is a qualitative research with 20 key informants and supporters taken using purposive sampling. Data collection methods were interviews, Discussion Group Forums (FGD). The results of the analysis showed that there was no regional policy regarding increasing the MSS for the Productive Age in Bogor City, but an early detection program for risk factors for non-communicable diseases had been carried out, implementing human resources were available but the needs were still lacking. , cross-sector support is quite good but there is no strategic division of roles, infrastructure and funding still need to be improved for services. A draft of policy recommendations has been prepared to increase Productive Age SPM Achievements in the City of Bogor with the Paguyuban Salapan Innovation Program